Analisis Pengolahan Air Limbah Rumah Pemotongan Hewan Ampel Kabupaten Boyolali - 'Alal Mu'miniina, Adzillatin; Windraswara, Rudatin (HIGEIA (Journal of Public Health Research and Development), 2021)
In 2018, the wastewater collected from outlet of RPH Ampel Boyolali WWTP fail to meet the standard set by the government. This study aims to analyze wastewater treatment process in this WWTP. This study is a qualitative descriptive with in-depth interviews, observation and testing of wastewater samples. The informants consist of 4 people who were selected by purposive and snowball sampling technique. Data collection was done by in-depth interviews, waste water samples test with sample collected using a composite time sampling method, and close observation, then analyzed qualitatively. Result showed that only TSS, pH, and 2nd day MPN Coliform parameters met the quality standard, while BOD5, COD, FOG, Ammonia and 1st and 3rd day Coliform MPN had not met the standard. RPH Ampel WWTP utilize gravity and biological processes for its treatment. RPH Ampel has no appointed staff who are specialized in managing wastewater and its treatment process. In conclution, WWTP is yet to meet the effluent standard set by the government. Interventions is needed to improve WWTP removal efficiency. Keywords: Slaughterhouses, quality of wastewater, processing of wastewater treatment.